Antioxidant Activity of Satureja hortensis L. Essential Oil and its Application in Safflower Oil - A Fathi; MA Sahari; M Barzegar; H Naghdi Badi (Institue of Medicinal Plants, ACECR, 2013)
Background: It has been considered by researchers to study the possibility of replacing chemical food additives (synthetic antioxidants) by natural products (medicinal plants). Objective: This study investigated the antioxidant properties of Satureja hortensis L. essential oil (SHEO) on safflower oil oxidation. Methods: Different assays have been used to evaluate the antioxidant activity of SHEO: total phenol content (TPC), DPPH•, ABTS+•, ferric thiocyanate (FTC), β - carotene bleaching. For evaluation of SHEO effect on safflower oil oxidation, peroxide value (PV), conjugated dienes (CD), and tiobarbituric acid (TBA) indices were compared with BHT (a synthetic antioxidant). Results: TPC of SHEO was determined to be 293.7 mg gallic acid equivalent in 1 ml of sample and IC50 was 0.71 mg/ml in DPPH•. 0.4 and 0.1 mg/ml of SHEO at all time (1, 5, 10, 15 min) showed the highest and lowest antiradical ABTS°+ activity (118.2 and 26.6 μg/ml AscAE =Ascorbic acid equivalent) in 15 min. In FTC and FTC-TBA, 8 mg/ml SHEO showed the highest activity. In β-carotene bleaching of 0.1-2 mg/ml SHEO, 0.1 has the minimum (%9.02), and 1 and 2 has the maximum inhibitory effects (%34.33 and %36.86 inhibitions). 4 mg/ml of SHEO had the highest inhibitory effect in the safflower oil test and that peroxide does not have significant difference with 0.1 mg/ml BHT. Conclusion: Antioxidant activities of SHEO concentrations increased in all indices (p< 0.05) and various concentrations were able to slow down the oxidation process.